411 The Cost of a Single Sport-Related Concussion in Adolescent Athletes. (April 2023) - Liles, David Campbell; Tang, Alan Ruigang; Williams, Kristen; Yengo-Kahn, Aaron Michael; Zuckerman, Scott L.; Terry, Douglas
Abstract : INTRODUCTION: Despite the ubiquity of sport-related concussions (SRC), the healthcare costs incurred by a single SRC are unknown. METHODS: We conducted a retrospective cohort study examining concussed athletes ages 12-23 who presented to a multi-disciplinary concussion center between 11/2017-10/2020. Athletes presenting for treatment more than 10 days post-injury and those sustaining >1 concussion during the study period were excluded. The primary outcome was the direct cost of the concussion care episode, derived by matching visit and imaging dates with institution inflation-adjusted cost data. A multivariable linear regression examined predictors of total concussion care costs. Independent variables included relevant demographics, medical/family medical history, injury characteristics, and initial Post-Concussion Symptom Scale (PCSS) score. RESULTS: In total, 710 athletes were included. Median age was 16.1 years (IQR = 15.1-17.2; 66.5% male). Median initial PCSS was 26 (IQR = 6-39). Sports with the highest prevalence of SRC were football (n = 261, 36.8%), soccer (n = 102, 14.4%) and basketball (n = 97, 13.7%). The mean cost of an SRC care episode was 822 (SD = 1, 233). The mean costs associated with a softball-related concussion were highest (M = 2, 372, SD = 4, 707), followed by basketball (M = 1, 012 SD = 1, 863), lacrosse (M = 924, SD = 1, 101), and football (M = 814, SD = 993). A multivariable linear regression showed that higher initial PCSS (b = 4.87, 95% CI = 1.32-8.42, p = .007), number of prior concussions (b = 118.79, 95% CI = 42.71-194.88, p = .002), and having an emergency department/urgent care visit (b = 670.20, 95% CI = 497.66-842.74) were significant predictors of greater cost. CONCLUSIONS: With a mean value of 822 per SRC, healthcare costs associated with this common injury total over 3 billion annually in the U.S. Greater costs were associated with higher initial symptom burden, prior concussion history, and emergency department/urgent care utilization. A nuanced understanding of cost-driving factors associated with SRC is a prerequisite to understanding cost-effectiveness of prevention and treatment.